Validitas Media Pembelajaran Audio Berbasis Podcast Spotify - Najla Aulia Putri Yazman; Armiati Armiati (Universitas Negeri Padang, 2023)
Based on the results of observation an interviews, learning media used when the covid-19 pandemic is limited to the use of e-book for students to learn independently and there was no explanation of direct material by the teacher. This research aimed to develop podcast-based audio learning media in the subject of Otomatisasi Tata Kelola Kepegawaian class XII OTKP. The method of research was a development research by using ADDIE model. The application of this model only used the analysis, design, and development. The data collection technique were interviews and validation sheet. Data analysis technique used descriptive quantitative. The research results show that podcast-based audio learning media on Spotify have met valid criteria, with assessment details of 93% on material aspects and 75% on media aspects. Based on the results, it was concluded that the learning media based audio podcast Spotify can be used as learning media.